Nonnegative solutions of two-point boundary value problems for nonlinear second order integrodifferential equations in Banach spaces. (1991) - Guo, Dajun
Abstract : In this paper, we combine the fixed point theory, fixed point index theory and cone theory to investigate the nonnegative solutions of two-point BVP for nonlinear second order integrodifferential equations in Banach spaces. As application, we get some results for the third order case. Finally, we give several examples for both infinite and finite systems of ordinary nonlinear integrodifferential equations.